Preparation and Characterization of Bentonite Gel - Hongbin, Wang; Guiquan, Feng; Haiyun, Chen; Jing, Zhang; Min, Yang (Asian Journal of Chemistry, 2011)
This method involves the preparation of bentonite gel from the samples of Wenshan Ca-bentonite of Yunnan. The reaction conditions are as follows: 4 % sodium oxalate; density of pulp is 15 %; the phosphate agent is sodium hexametaphosphate, its dosage is 0.5 %, the gelling agent is magnesium oxide; the result:the cation-exchange capacity is 104 mmol/100 g soil, the content of montmorillonite is 98 %, the colloid index is 100 mL/g soil, the expansion rate is 93 mL/g soil.